HUBUNGAN EMPHATY (EMPATI) PETUGAS KESEHATAN DENGAN KEPUASAN PASIEN RAWAT JALAN PADA MASSA PANDEMI COVID-19 DI PUSKESMAS RAMBUNG BINJAI SELATAN TAHUN 2022 - Eliza Bestari Sinaga; Fifi Ria Ningsih Safari (Universitas Prima Indonesia, 2022)
The quality of health services is multi-dimensional. Judging from the users of health services, the notion of service quality is more related to the responsiveness of officers to meet patient needs, smooth communication between officers and patients. Empathy is a tendency to understand the condition or state of mind of others, the slightest changes and responses in patients must be understood, because they must understand the patient's condition, health workers must have empathy. The purpose of this study was to determine the relationship between the empathy of health workers and patient satisfaction during the COVID-19 pandemic at the Rambung Binjai Selatan in 2022. This type of research was descriptive analytic using a cross sectional design. The population in this study were patients who visited the Puskesmas Rambung Binjai Selatan during the Covid-19 pandemic starting from January to July 2022 totaling 2,800 people with an average of 250 people per month. The sample is the part taken from the whole object under study and is considered to represent the entire population. Sampling is a sampling technique with certain considerations desired by the researcher (objective / problem in research) so that the sample can represent the characteristics of the population that have been known previously. The sampling method used the Purpose Sampling method as many as 96 samples. The result of the study is that there is a relationship between empathy and patient satisfaction during the Covid-19 pandemic at the Rambung Binjai Selatan Health Center with a p value of 0.003. Researchers suggest that in the future health workers can provide more empathy for patients who come for outpatient care so that they can be used as examples for other officers and so that patients who come are satisfied in getting the services they receive